The burden of diseases and risk factors in Bangladesh, 1990-2019: a systematic analysis for the Global Burden of Disease Study 2019 - Islam, Sheikh Mohammed Shariful; Uddin, Riaz; Das, Subasish; Ahmed, Syed Imran; Bin Zaman, Sojib; Alif, Sheikh Mohammad; Hossen, Md Tanvir; Sarker, Malabika; Siopis, George; Livingstone, Katherine M.; Mehlman, Max L.; Rahman, Md Marufur; et al. (The lancet. Global health, 2023)
Background Bangladesh has made substantial progress in improving socioeconomic and health indicators over the past 50 years, but data on national disease burden are scarce. We used data from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2019 to estimate the burden of diseases and risk factors in Bangladesh from 1990 to 2019.Methods For this systematic analysis, we analysed data from vital registration systems, surveys, and censuses using multistage modelling processes to estimate life expectancy at birth, mortality rate, years of life lost (YLLs), years lived with disability (YLDs), and disability-adjusted life-years (DALYs). Additionally, we compared the health status of Bangladesh with that of the other countries in the GBD south Asia region-Bhutan, India, Nepal, and Pakistan.Findings Life expectancy at birth in Bangladesh increased from 58 center dot 2 years (95% uncertainty interval 57 center dot 1-59 center dot 2) in 1990 to 74 center dot 6 years (72 center dot 4-76 center dot 7) in 2019. Between 1990 and 2019, the age-standardised mortality rate decreased from 1509 center dot 3 (1428 center dot 6-1592 center dot 1) to 714 center dot 4 (604 center dot 9-838 center dot 2) deaths per 100 000 population. In 2019, non-communicable diseases represented 14 of the top 20 causes of death; the leading three causes were stroke, ischaemic heart disease, and chronic obstructive pulmonary disease. High blood pressure, high fasting plasma glucose, and smoking were the top three risk factors. From 1990 to 2019, the rate of all-cause DALYs decreased by 54 center dot 9% (48 center dot 8-60 center dot 4). In 2019, the leading causes of DALYs and YLLs were neonatal disorders, stroke, and ischaemic heart disease, whereas musculoskeletal disorders, depressive disorders, and low back pain were the leading causes of YLDs. Bangladesh has the lowest age-standardised rates of mortality, YLDs, and YLLs and the highest life expectancy at birth in south Asia.Interpretation Over the past 30 years, mortality rates have reduced by more than half in Bangladesh. Bangladesh must now address the double burden of communicable and non-communicable diseases. Cost-effective, multisectoral efforts are needed to prevent and control non-communicable diseases, promote healthy lifestyles, and prevent premature mortality and disabilities.Funding Bill & Melinda Gates Foundation.Copyright (c) 2023 The Author(s). Published by Elsevier Ltd. This is an Open Access article under the CC BY 4.0 license.